Clinico-physiological studies of atropine-tiletamine-zolazepam-sevofluraneanaesthesia with or without dexmedetomidine premedication in dogs - TIWARI, KANIKA; JADON, NARENDRA SINGH; PANDEY, PRIYANKA; KANDPAL, MANJUL (The Indian Journal of Animal Sciences, 2024)
The present study was conducted on twelve dogs randomly divided into two groups, viz. group A and B irrespective of age, breed and sex. Animals of group A were premedicated with atropine sulphate at the dose rate of 0.04 mg/kg body weight subcutaneously while in group B, atropine sulphate at the dose rate of 0.04 mg/kg body weight subcutaneously and dexmedetomidine at the dose rate of 5µg/kg body weight intravenously were administered at 5 min interval. Tiletamine-zolazepam was administered intravenously as induction agent and maintenance with sevoflurane in both the groups of animals. Clinico-physiological, haemodynamic and biochemical parameters were evaluated at various time intervals. Induction time was significantly lower whereas duration of anaesthesia, recovery time and complete recovery time were significantly higher in animals of group B as compared to group A. Excellent muscle relaxation and good analgesia was observed in the animals of group B. Abolition of pedal reflex and palpebral reflex was better in the animals of group B as compared to group A. Physiological parameters fluctuated within the normal limits. Significant decrease in PR interval and significant increase in QRS interval was recorded in the animals of group A. Non-significant changes were observed in the biochemical parameters except significant increase in the serum glucose level was observed at 30 min to 1 h in both the groups of animals. Thus, it was concluded that the anaesthetic combination of atropine-dexmedetomidine-tiletamine-zolazepam-sevoflurane produces better sedation, muscle relaxation and analgesia as compared to atropine-tiletamine-zolazepam-sevoflurane anaesthesia.